Produção e aplicação de biossurfactante de Starmerella bombicola ATCC 222214 no tratamento de efluente e sistemas contaminados com petroderivados. - Oliveira, Kaio Wêdann de (2025)
Fuel and lubricating oil spills that occur in industries during the refueling of machines, storage tanks and the washing of tanks and equipment are the main causes of the accumulation of petroleum derivatives in the environment. Due to human activities, petroleum derivative spills are among the main causes of soil and water pollution, causing drastic changes in the microbiological, chemical and physical properties of the soil and surface. Thus, the application of natural surfactants emerges as an attractive and efficient solution among the innovative technologies for cleaning oil storage tanks and for the treatment of contaminated soils and industrial effluents. Therefore, this study aimed to evaluate the production and application of a biosurfactant produced by the yeast Starmerella bombicola ATCC 222214, in the decontamination of marine and terrestrial environments contaminated by oil. The production of the biosurfactant by the yeast was evaluated by observing the effect of different carbon/nitrogen sources and culture conditions in flasks. The removal power of hydrophobic compounds by the action of the biosurfactant in different types of soils (clayey and silty) and standard sand was evaluated. The destabilization power of heavy oil OCB1, diesel and engine oil on smooth surfaces, as well as the removal capacity of oil from industrial effluent by the biosurfactant were studied. From the most promising surfactant properties, the culture medium supplemented with 2.0% glucose and 5.0% glycerol, the speed of 200 rpm, the fermentation time of 180 hours and the inoculum size of 5.0% were selected. The yield of the isolated biosurfactant was 1.5 g/L. The emulsification rates of engine oil and diesel oil were 86.6 ± 0.22% and 51.7 ± 0.15%, respectively, indicating affinity of the biomolecule for complex hydrocarbons. In stability tests performed at different pH values, temperature and NaCl concentration, the surface tension ranged from 25.82 to 32.30 mN/m. The Critical Micellar Concentration (CMC) was 0.4 g/L, at which concentration the surface tension reached 26.85 mN/m. In the kinetic tests, the biosurfactant removed 82.48 ± 0.12, 97.61 ± 0.01 and 99.01 ± 0.02% of the engine oil adsorbed on sand, silty soil and clayey soil, while in the static test in packed columns the removals were 72.05 ± 0.80, 96.87 ± 0.30 and 99.50 ± 0.03%, respectively. The biosurfactant produced in this study proved to be a promising agent for environmental remediation applications in the oil and energy sector, as well as in industrial areas contaminated by oil and derivatives.